1997
DOI: 10.1117/12.274304
|View full text |Cite
|
Sign up to set email alerts
|

<title>Capillary-blood-flow monitoring using laser speckle contrast analysis (LASCA): improving the dynamic range</title>

Abstract: We have developed a technique, called Laser Speckle Contrast Analysis (LASCA), to monitor capillary blood flow. Like the earlier method 'single-exposure speckle photography' it uses the phenomenon of time-varying speckle, drawing on models that relate the statistics ofthe speckle pattern, especially the contrast, to the velocity ofthe scatterers. Temporal variations in the pattern blur the captured image, whether photographic or digital, reducing the contrast. LASCA is a fully-digitized, fullfield, non-invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 2 publications
(2 reference statements)
0
13
0
Order By: Relevance
“…The technique ingeniously utilizes the two-dimensionality of the speckle pattern and, at this point, it is of considerable use for future applications in comparison with point measurements by the laser Doppler or biospeckle technique. The photographic process is certainly disadvantageous for practical uses, but Briers and his co-workers 71,72 have recently developed a fully digitized imaging/processing technique called ''laser speckle contrast analysis (LASCA),'' instead of using photography. This approach may be one of the promising steps in the development of this technique.…”
Section: Speckle Photographymentioning
confidence: 99%
“…The technique ingeniously utilizes the two-dimensionality of the speckle pattern and, at this point, it is of considerable use for future applications in comparison with point measurements by the laser Doppler or biospeckle technique. The photographic process is certainly disadvantageous for practical uses, but Briers and his co-workers 71,72 have recently developed a fully digitized imaging/processing technique called ''laser speckle contrast analysis (LASCA),'' instead of using photography. This approach may be one of the promising steps in the development of this technique.…”
Section: Speckle Photographymentioning
confidence: 99%
“…Richards and Briers [45] showed that contrast images obtained using LASCA give a good picture of the movement of red blood cells in the hand of a volunteer. Cheng and Duong [56] and Konishi et al [34] even used LSI and LSFG respectively to map the ocular blood flow in the retina.…”
Section: Applicationsmentioning
confidence: 99%
“…Richards and Briers [44,45] suggested this was due to an offset in the pixel values termed pedestal and introduced by the CCD camera. Manually removing this offset resulted in an increase in contrast from 0.41 to 0.95 for a static speckle pattern.…”
Section: Laser Speckle Contrast Analysis (Lasca)mentioning
confidence: 99%
See 2 more Smart Citations